2017
DOI: 10.1016/j.hal.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated CO2 on phytoplankton community biomass and species composition during a spring Phaeocystis spp. bloom in the western English Channel

Abstract: A 21-year time series of phytoplankton community structure was analysed in relation to Phaeocystis spp. to elucidate its contribution to the annual carbon budget at station L4 in the western English Channel (WEC).Between 1993-2014 Phaeocystis spp. contributed $4.6% of the annual phytoplankton carbon and during the March À May spring bloom, the mean Phaeocystis spp. biomass constituted 17% with a maximal contribution of 47% in 2001. Upper maximal weekly values above the time series mean ranged from 63 to 82% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…A variable response in Phaeocystis spp. to elevated pCO 2 has also been reported with increased growth (Chen et al, 2014;Keys et al, 2017), no effect (Thoisen et al, 2015) and decreased growth (Hoogstraten et al, 2012) observed. Phaeocystis spp.…”
Section: Community Compositionmentioning
confidence: 78%
“…A variable response in Phaeocystis spp. to elevated pCO 2 has also been reported with increased growth (Chen et al, 2014;Keys et al, 2017), no effect (Thoisen et al, 2015) and decreased growth (Hoogstraten et al, 2012) observed. Phaeocystis spp.…”
Section: Community Compositionmentioning
confidence: 78%
“…Figure visualizes the steep increase of the oceanic sink for anthropogenic CO 2 (the anthropogenic CO 2 flux from the atmosphere to the ocean) for the period 1960–2018 . This remarkable increase (by a factor of approximately 3.5) suggests that marine phytoplankton may benefit from rising CO 2 levels, despite the widespread scarcity of iron and/or other nutrients in marine surface waters. , Recent studies have shown that phytoplankton may be more adaptable to the increasing atmospheric partial pressure of CO 2 (pCO 2 ) than previously thought, with the limitation that different species react differently. In Subarctic and Arctic waters, prymnesiophytes (including coccolithophores) are negatively impacted, whereas small picoeukaryotes benefit from increasing pCO 2 . There is also evidence that diatoms, which play a key role in the biological carbon pump, show a statistically significant increase in growth rate in response to rising atmospheric CO 2 whereby larger diatom species tend to have a more pronounced growth rate enhancement in response to elevated CO 2 partial pressure than smaller ones. Moreover, it has also been shown that increasing CO 2 levels improve cyanobacterial growth and increase cyanobacterial biomass …”
Section: Earth’s Biosphere: a Sink For Anthropogenic Co2mentioning
confidence: 94%